Three-Tiered Defensive System and Ethnic Fusion: A Study of Architectural Art in Guomari Fortress, Eastern Qinghai - Liyue Wu; Qinchuan Zhan; Yanjun Li (Buildings)
Guomari fortress in eastern Qinghai Province exemplifies vernacular architecture shaped by multiethnic interaction, environmental adaptation, and localized defense strategies. Originally a Ming Dynasty military-agricultural outpost, it evolved into a Tu ethnic settlement. Fieldwork, including architectural surveys and spatial analysis, identified a three-tiered defensive system: (1) strategic use of terrain and rammed-earth walls; (2) labyrinthine alleys with L-, T-, and cross-shaped intersections; and (3) interconnected rooftops forming elevated circulation routes. Courtyards are categorized into single-line, L-shaped, U-shaped, and fully enclosed layouts, reflecting adaptations to terrain, ritual functions, and thermal needs. Architectural features such as thick loam-coated walls and flat roofs demonstrate climatic adaptation, while the integration of Han timber frameworks, Tibetan prayer halls, and Tu decorative elements reveals cultural convergence. Traditional craftsmanship, including carved wooden scripture blocks and tsampa-based murals, is embedded within domestic and ritual spaces. The fortress’s circulation patterns mirror Tibetan Buddhist cosmology, with mandala-like alleys and rooftop circumambulation routes. These findings offer insights into vernacular resilience and inform conservation strategies for multiethnic fortified settlements.